The Importance of Dietary Fiber on Stress Hormone in Pregnancy: A Literature Review - Helena Fabiani; Henny Tannady Tan (Universitas Andalas, 2020)
Antepartum depression is a mental health issue that is frequently ignored and often leads to suicidal behaviours. The harmful effects of antepartum depression are not only experienced by mothers, but also by children in the future. Depression due to pregnancy is usually attributed to several causes, including the biological component. Biological shifts that arise during gestation interrupt the maternal stress protection mechanism, one of which is the dysregulation of the hypothalamus-pituitary-adrenal axis (HPA-axis) resulting in hypersecretion of cortisol. Excessive release of cortisol as a stress hormone has been correlated with depressive symptoms, particularly throughout pregnancy. Recently, dietary factors, in particular dietary fiber, have become of concern as component that is recognized to attenuate stress hormones. The dietary fiber that is ingested will be digested by intestinal bacteria and will produce short-chain fatty acids as the essential metabolites. These metabolites are known to play a role in various brain functions, including HPA-axis through various means. The objective of this research is aimed at determining the function of dietary fiber within cortisol as a biomarker of the central stress response system, particularly throughout pregnancy.